SUSTAINABLE POWER: ENHANCING PARK MICROGRIDS WITH HYBRID ENERGY STORAGE TECHNOLOGIES - admin, admin; Zhou , Wei Hua (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
The multi-circuit coupling transmission mode is an inevitable trend of power grid construction, mainly with partially coupled multi-circuit lines. Affected by the local coupling between lines, the existing fault location methods have large errors. To this end, fault analysis and fault location methods are carried out on partially coupled double-circuit transmission lines. According to the structure and characteristics of the partially coupled double-circuit transmission line on the same tower, the voltage and current interface equations at the coupling demarcation point of the partially coupled double-circuit transmission line are established using line decoupling theory. On this basis, a timedomain analysis model of fault location for each coupling section is constructed, and a time-domain method for fault location of partially coupled double-circuit transmission lines is proposed. Finally, the electromagnetic transient simulation software is used to construct a partially coupled double-circuit transmission line model on the same tower, and a comprehensive simulation verification is performed. The results show that the proposed method has high accuracy.